Factors associated with sex in the context of methamphetamine use in different sexual venues among HIV-positive men who have sex with men - Zians Jim; Strathdee Steffanie A; Semple Shirley J; Patterson Thomas L (BMC, 2010)
Abstract Background Harm reduction has focused primarily on reduction of high-risk substance using behaviors rather than reductions in high-risk sexual behaviors. Furthermore, most studies focus on individual behavior change, with less attention paid to the social and environmental context. This paper promotes understanding of the interplay between the individual and the social context by examining the psychosocial and behavioral characteristics of 321 methamphetamine-using HIV-positive men who have sex with men (MSM) in San Diego, CA based on the locations or venues of their sexual activities when "high" on methamphetamine. Methods Participants in a safer-sex intervention study underwent a baseline assessment that queried demographic and psychosocial characteristics as well as drug use and sexual risk behaviors. For purposes of analysis, respondents were classified according to their preference of sexual venue: private (e.g., home), commercial (e.g., bathhouse), or public (e.g., public park or restroom). Results The commercial venue group was younger, better educated, more likely to identify as gay, and significantly more likely to have used "club drugs" as compared to the other two groups. Men in the commercial- and public-venue groups reported more high-risk sex compared to the private-venue group. The public-venue group reported heavier drug and alcohol use, had significantly higher Beck depression scores, reported more experiences of stigma, and scored higher on a measure of sexual compulsivity than did the other two groups. Conclusion In an effort to reduce HIV/STI risk-behaviors, future studies should investigate the feasibility of modifying personal, psychosocial and structural factors associated with the use of risky sexual venues where HIV-positive methamphetamine users engage in sexual activity when "high" on methamphetamine. Trial registration ClinicalTrials.gov NCT00432926